The phycoerythrobilin isomerization activity of MpeV in Synechococcus sp. WH8020 is prevented by the presence of a histidine at position 141 within its phycoerythrin-I β-subunit substrate - Carrigee, Lyndsay A.; Frick, Jacob P.; Liu, Xindi; Karty, Jonathan A.; Trinidad, Jonathan C.; Tom, Irin P.; Yang, Xiaojing; Dufour, Louison; Partensky, Frédéric; Schluchter, Wendy M. (Frontiers in Microbiology, 2022)
Marine Synechococcus efficiently harvest available light for photosynthesis using complex antenna systems, called phycobilisomes, composed of an allophycocyanin core surrounded by rods, which in the open ocean are always constituted of phycocyanin and two phycoerythrin (PE) types: PEI and PEII. These cyanobacteria display a wide pigment diversity primarily resulting from differences in the ratio of the two chromophores bound to PEs, the green-light absorbing phycoerythrobilin and the blue-light absorbing phycourobilin. Prior to phycobiliprotein assembly, bilin lyases post-translationally catalyze the ligation of phycoerythrobilin to conserved cysteine residues on alpha- or β-subunits, whereas the closely related lyase-isomerases isomerize phycoerythrobilin to phycourobilin during the attachment reaction. MpeV was recently shown in Synechococcus sp. RS9916 to be a lyase-isomerase which doubly links phycourobilin to two cysteine residues (C50 and C61; hereafter C50, 61) on the β-subunit of both PEI and PEII. Here we show that Synechococcus sp. WH8020, which belongs to the same pigment type as RS9916, contains MpeV that demonstrates lyase-isomerase activity on the PEII β-subunit but only lyase activity on the PEI β-subunit. We also demonstrate that occurrence of a histidine at position 141 of the PEI β-subunit from WH8020, instead of a leucine in its counterpart from RS9916, prevents the isomerization activity by WH8020 MpeV, showing for the first time that both the substrate and the enzyme play a role in the isomerization reaction. We propose a structural-based mechanism for the role of H141 in blocking isomerization. More generally, the knowledge of the amino acid present at position 141 of the β-subunits may be used to predict which phycobilin is bound at C50, 61 of both PEI and PEII from marine Synechococcus strains.